Role of Adding Topical Metronidazole in the Treatment of Acute Anal Fissure - Ali, Shayda; Sultana, Fouzia; Khan Lodi, Russel Ahmed; Paul, Tapesh Kumar; Bari, Khaleda Nazneen (Delta Medical College Journal, 2024)
Background: An anal fissure is a longitudinal ulcer in the anoderm of the distal anal canal which extends from the anal verge proximally towards, but not beyond, the dentate line. Anal fissure is a disease characterized by severe pain in the anorectal region with constipation, per rectal bleeding and sometime itching. Recently, anaerobic bacteria are sorted out as a causative factor. Objective: This study investigates patient compliance in the treatment of anal fissure with adding topical metronidazole. Materials and method: A total number of 100 patients attended to the General Surgery Clinic of Delta Medical College Hospital, Department of Surgery, between December 2020 and May 2021 and diagnosed with acute anal fissure were included in this prospective study. Patients older than 18 years, including non-pregnant, pregnant and lactating women are recruited. Patients were randomly divided in two groups. One group (group: 1) was treated with topical glyceryl trinitrate [0.4% nitroglycerin ointment], and the other group (group: 2) was treated with topical glyceryl trinitrate [0.4% nitroglycerin ointment] and topical antibiotic [metronidazole 0.75%]. Results: There is no difference between the groups regarding age and symptoms. From week 1, fissure healing rates were high in group 2. Group 2 VAS score levels were lower than group 1 and achieved by group 1 only in week 4. Compliance of pregnant and lactating lady was more in group 2. Conclusion: Adding topical metronidazole to treatment of acute anal fissure reduces the duration and severity of pain, shortens healing time and increases the healing rate. Delta Med Col J. Jan 2021;9(2): 84-90